EFEKTIFITAS METODE PEMBELAJARAN BERBASIS PROYEK (PROJECT BASED LEARNING) UNTUK MENINGKATKAN KEMAMPUAN PENGEMBANGAN DIRI MAHASISWA - AMINULLAH AMINULLAH; SITI SOLIHUN (GANEC SWARA, 2024)
The aim of this research is to describe the effectiveness of project-based learning methods to improve students' self-development abilities. This research method is quantitative research with a descriptive design. This research was carried out at the Faculty of Fisheries in the odd semester 2024/2025 with a total of 22 students, especially in Mathematics courses. The research results show that the project-based learning method is effective in improving students' self-development abilities in mathematics learning, especially in the cognitive and affective domains. Increased self-development abilities in the cognitive domain, from initially the average student score of 72.18 to 82.86. Meanwhile, in the cognitive domain, initially the average student score was 79.55 to 84.64. The average value of the students' self-development abilities is included in the effective category for the learning methods used.